Importance of the Research and Evidence-Based Practice in the Undergraduates - Nahid Jamal; Abid Abbasi; Hunain Ali Faiz (ziauddin University, 2024)
I am writing this letter to highlight the importance of research and evidence-based practice among nursing undergraduate students in Pakistan. Nurses are the backbone of the healthcare system and build a strong foundation for any healthcare needs in the hospital setting. Research and Evidence-based clinical practice are crucial parts of a nursing career, to be able to promote better evidence-based practice, research needs to be taught in nursing undergraduate programs to ensure high-quality practice1. The core focus is to determine the role of evidence-based practices in reducing bedsores in the clinical sector. According to this aspect, undergraduate nursing students can provide quality care to patients as well as can be able to incorporate evidence-based practices in their professional lives